2004
DOI: 10.1007/bf03166479
|View full text |Cite
|
Sign up to set email alerts
|

A study of discharge fluctuations in magnetically-supported dc discharge in cylindrical and inverted cylindrical configuration

Abstract: Abstract.We have investigated apparently stochastic fluctuations of magnetically-supported dc discharge in cylindrical coaxial configuration. In the system the electric field had radial direction while the magnetic field was applied axially. The discharge vessel length was 12 centimetres. Working gas was typically argon at pressure of several Pa, magnetic field 10-50 mT.The contribution describes experimental results -frequency and phase analysis of the instabilities, which we detected in our experimental syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This is due to the instabilities that develop in the dc discharge and the amplitude of which at higher magnetic fields rises. Preliminary studies of the power spectra of these fluctuations [11], [12] have shown that they can be possibly characterized as the non-linear ionization-drift turbulence of similar kind as described by Lin and Wu in [21].…”
Section: Resultsmentioning
confidence: 98%
“…This is due to the instabilities that develop in the dc discharge and the amplitude of which at higher magnetic fields rises. Preliminary studies of the power spectra of these fluctuations [11], [12] have shown that they can be possibly characterized as the non-linear ionization-drift turbulence of similar kind as described by Lin and Wu in [21].…”
Section: Resultsmentioning
confidence: 98%